The Sexual Subjectivity of Women, Agency, and Empowerment: A Critical Conceptual Analysis - Miroslava Šudila Žilinská; Gabriel Bianchi (Gender a Výzkum)
Sexual subjectivity in women together with sexual agency and empowerment have been receiving growing attention in sex research in recent decades. In this article we highlight the conceptual uncertainty and challenges research field, mostly in the context of #MeToo initiatives and the current discussion around understanding sexual violence in Czech Republic and the Slovak Republic. We propose a conceptual map, in which we show the key role of sexual subjectivity for sexuality research, in contrast to other terms, such as sexual self--concept or sexual self-schema. We demonstrate how the important conceptual components of subjectivity, sexual agency, and empowerment have been misunderstood in the postfeminist and neoliberal discourse and have brought new forms of oppression to female sexuality - in the forms of the agency imperative and pseudoempowerment. The article offers an integrated conceptual framework for female sexual subjectivity based on a critical reflection of existing sexuality research from the perspective of second-order psychology as opposed to mainstream positivist approaches. We propose adopting approaches to sexual subjectivity that (1) allow us to reflect on the dynamics of intrapersonal and interpersonal scripting rooted in normative social and cultural contexts, while (2) allowing for the authentic experience of lived, selfgenerated, and diverse subjectivities.